Requisitos de un Sistema de Información para Gestión de Patrimonio - Mª Victoria Luzón; Domingo Martín Perandrés; Germán Arroyo; José Ramón López Rodríguez; Julia Herce Fimia; Rocío Izquierdo de Montes; Álvaro Jiménez Sancho; Juan Bosco Martínez Mora; Marta Pérez Falcón; Francisco Lamolda Álvarez; Elena Correa Gómez; Ramón Rubio Domene (Virtual Archaeology Review)
Cultural Heritage has had a great development in recent years. Currently, new tools are being developed as a result of transferring knowledge between areas. One of these possibilities is to create a system for Cultural Heritage with the advantages of Geographic Information System. The difficulties are not trivial, being the first step to create a framework of common requirements for the multiple needs that may arise. We present a set of requirements that provide that objective, obtained from the study of the needs of various restoration and Cultural Heritage professional teams.